Cyberbullying Pada Peserta Didik SMP Negeri 5 Pangkalpinang - Elpemi, Nopia; Nikmarijal, Nikmarijal (IJoCE: Indonesian Journal of Counseling and Education, 2023)
The development of information and communication technology makes it easier for users in various ways. One of them is the ease of communicating without the barriers of distance, time and place. However, sometimes in communicating not everyone applies the same norms by communicating so that cyberbullying can occur. At Junior High School number 5 Pangkalpinang, cyberbullying has occurred in the form of students' actions disseminating videos of fights between other students on social media. The method used in this research is quantitative with the data collection method using a questionnaire which was developed through forms of cyberbullying according to Robert Kowalski. As for the scoring format, it follows from the Revised Cyber Bullying Inventory (RCBI) compiled by Topcu and Backer. In processing the data, researchers used descriptive statistics. The respondents involved in this study amounted to 274 students. This study aims to find out the description of cyberbullying on students of Junior High School number 5 Pangkalpinang. The results showed that the level of students at Junior High School number 5 Pangkalpinang was in the low category, 273 students and 1 student was in the medium category. With details of 46 students who have never been involved in cyberbullying and 228 others who have been involved in cyberbullying. The highest form of cyberbullying is harassment.